Stroke outcome related to initial volume status and diuretic use - Renner, Christopher; Kasner, Scott E.; Bath, Philip M.; Bahouth, Mona N.; Diener, Hans-Christoph; Hacke, Werner; Hennerici, Michael G. (Journal of the American Heart Association, 2022)
Background: We hypothesized that stroke outcome is related to multiple baseline hydration-related factors including volume contracted state (VCS) and diuretic use. Methods and Results We analyzed a prospective cohort of subjects with ischemic stroke <24 hours of onset enrolled in acute treatment trials within VISTA (Virtual International Stroke Trials Archive). A VCS was defined based on blood urea nitrogen-to-creatinine ratio. The primary end point was modified Rankin Scale score at 90 days. Primary analysis used generalized ordinal logistic regression over the mRS range, adjusted for Totaled Health Risks in Vascular Events score, onset-to-enrollment time, and thrombolytic use. Of 5971 eligible patients with stroke, 42% were taking diuretics at the time of hospitalization, and 44% were in a VCS. Patients in a VCS were older, had more vascular risk factors, were more likely taking diuretics, and had more severe strokes. Diuretic use was associated with both reduced chance of achieving a good functional outcome (odds ratio [OR], 0.57 [95% CI, 0.52-0.63]) and increased mortality at 90 days (OR, 2.30 [95% CI, 2.04-2.61]). VCS was associated with greater mortality 90 days after stroke (OR, 1.53 [95% CI, 1.33-1.76]). There was no evidence of effect modification among the 3 exposures of VCS, diuretic use, or hypokalemia in relation to outcome. Conclusions: A VCS at the time of hospitalization was associated with more severe stroke and odds of death but not associated with worse functional outcome when accounting for relevant characteristics. Diuretic use and low serum potassium at the time of stroke onset were associated with worse outcome and may be worthy of further investigation.
Gesehen am 28.11.2023